Challenges and Opportunities in the .New Millennium - Financial Sector Perspective - Majmudar, Suchint (Ushus Journal of Business Management, 2002)
The Indian financial sector has been buffeted by a recent global development in accounting and financial markets. Technology is enabling the financial sector to transfer funds and settle trades across borders in real times and novel financial instruments such as securitisation of debt and derivatives while extending the reach of investment manifold are also resulting in recycling of existing funds. This article examines recent trends in the financial sector and sums up the key issues facing Indian financial professionals.